EFEKTIVITAS MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN HASIL BELAJAR PADA SUBTEMA SUHU DAN KALOR SISWA KELAS V SD ISLAM PESANGGRAHAN SEMARANG - Nadia Amalia Dara Puspitasari Nadia; Qoriati Mushafanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background that prompted this research was to show that the learning level of students was still relatively low, so that there were still many students who scored below the KKM, student activities when learning was not active and the independence of students was still lacking.The problem of this research is "How is the effectiveness of the discovery learning learning model in Improving Learning Outcomes in the Sub-theme of Temperature and Heat for Fifth Grade Students at Pesanggrahan Islamic Elementary School?". The goal to be achieved in this study is to determine the effectiveness of the discovery learning model in improving learning outcomes in the Sub-theme of Temperature and Heat for Fifth Grade Students at Pesanggrahan Islamic Elementary School.This type of research is quantitative research with quantitative experimental methods and using Pre-Experimental Designs in the form of One-Group Pretest-Posttest Design. The population used in the study was all of class V for the 2023/2023 school year. The samples taken were 25 students using the Random Sampling Technique. The data in this study were obtained through tests, interviews and documentation.The results showed an increase in student learning outcomes after being treated using the discovery learning model which can be seen from the results of the pretest and posttest. The pretest average was 48,40 while the posttest average was 83,6. This is evidenced by a significance level of 5% indicating t count > t table, namely 30.04 > 2.060 meaning that Ho is rejected and Ha is accepted. So it can be concluded that the discovery learning learning model is effective in increasing learning outcomes in the Sub-theme of Temperature and Heat for Class V SD Islam Pesanggrahan students.Based on the results of the research, suggestions that can be conveyed are that the discovery learning model can be used as an alternative teacher in teaching to improve student learning outcomes.